(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
Parasitic roundworms (nematodes) cause substantial morbidity and mortality in livestock animals globally and considerable productivity losses to farmers. The control of these nematodes has relied largely on the use of a limited number of anthelmintics. However, resistance to many of these anthelmintics is now widespread, and, therefore, there is a need to find new drugs to ensure sustained and effective treatment and control into the future. The present study was undertaken to evaluate the anthelmintic activity of crude aqueous, Petroleum ether, chloroform and methanol extract Olea europaea leaves using Pheretima posthuma as test worms. Single concentration (5%) of extracts was tested in the bioassay, which involved the determination of the time of paralysis (P) and time of death (D) of the worms. Piperazine citrate was included as a standard reference and distilled water as a control. The results of the present study indicated that Olea europaea leaves extracts were exhibited anthelmintic activity significantly when compared with the standard (Piperazine citrate) group. Further studies are in process to isolate the active principles responsible for the activity.